2016
DOI: 10.1016/j.psyneuen.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in the pathophysiology of suicidal behavior

Abstract: Objective Immune dysregulation has been implicated in depression and other psychiatric disorders. What is less clear is how immune dysregulation can affect risk of suicidal behavior. We reviewed the scientific literature concerning cytokines related to suicidal ideation, suicidal behavior and suicide, and surveyed clinical and neurobiological factors associated with cytokine levels that may modulate effects of inflammation on suicide risk. Methods We searched PubMed, Embase, Scopus and PsycINFO for relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 122 publications
(231 reference statements)
6
128
0
5
Order By: Relevance
“…Alterations of the HPA axis, observed among individuals with suicidal ideation and depressive disorders, may well be one mechanism underlying the consistently observed statistical association of sleep disturbance and suicidal ideation. In a recent study, suicidal patients, as compared with their non-suicidal counterparts, were found to have chronic systemic inflammation, as evidenced by their higher plasma or serum concentrations of pro-inflammatory cytokines including interleukin-1β, interleukin-6, interleukin-10, C-reactive protein, and tumor necrosis factor-α [30]. In addition to these hypothesized neuroendocrine and proinflammatory mechanism, some investigators have posited that shared psychosocial and behavioral mechanisms, including adverse life events, psychiatric conditions and physical inactivity [26, 27] may explain the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the HPA axis, observed among individuals with suicidal ideation and depressive disorders, may well be one mechanism underlying the consistently observed statistical association of sleep disturbance and suicidal ideation. In a recent study, suicidal patients, as compared with their non-suicidal counterparts, were found to have chronic systemic inflammation, as evidenced by their higher plasma or serum concentrations of pro-inflammatory cytokines including interleukin-1β, interleukin-6, interleukin-10, C-reactive protein, and tumor necrosis factor-α [30]. In addition to these hypothesized neuroendocrine and proinflammatory mechanism, some investigators have posited that shared psychosocial and behavioral mechanisms, including adverse life events, psychiatric conditions and physical inactivity [26, 27] may explain the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the role of cytokines in suicidal behavior is contrary to what would be expected; previous evidence has suggested increases in interferon gamma (IFN)-γ, which down regulates the production of IgE. Moreover, an association between increased levels of IL-4 and suicide was only demonstrated in one study (121). Notwithstanding the foregoing results, IgE status has been associated with increased depression scores indicating worse mood symptoms (122).…”
Section: Aeroallergensmentioning
confidence: 85%
“…In regard to the type of depressive symptoms, Capuron et al only observed that IL-6 appeared to be related to the “reduced appetite” score of the Montgomery–Asberg Depression Rating Scale in elderly subjects [47]. Moreover, a recently published review concluded that IL-6 is the cytokine most robustly associated with suicidal ideation, suicides, and nonfatal suicide attempts [48], thereby suggesting an important role of this interleukin in this aspect of depression. The authors found that the results for other inflammatory parameters were inconclusive.…”
Section: Discussionmentioning
confidence: 99%